Differential susceptibility of invasive Haemophilus influenzae serotype a and serotype b to ampicillin and other commonly prescribed antibiotics. (1st August 2014) - Shuel, M.; Whyte, K.; Drew, T.; Wylie, J.; Lefebvre, B.; Hoang, L.; Tsang, R.S.W.
Abstract: Haemophilus influenzae serotype a (Hia) has become an important pathogen in the post‐ H. influenzae serotype b (Hib) vaccine era. Antibiotic resistance in H. influenzae is a global phenomenon, but few studies have looked at antibiotic resistance profiles with regard to serotype. Invasive Hia ( n = 157), noninvasive Hia ( n = 2) and invasive Hib ( n = 42) collected over the last two decades from three Canadian Provinces were examined for resistance to several commonly prescribed antibiotics, and sequence types (STs) were determined by MLST. Only 1·9% of Hia showed antibiotic resistance, while 31% of Hib were resistant to one or more antibiotic. Resistance to ampicillin, sulfamethoxazole–trimethoprim, chloramphenicol and tetracycline was observed, with β‐lactamase‐mediated ampicillin resistance being the most common. Nine STs were identified for Hia with 7 STs belonging to the same clonal complex. Ten STs were observed in Hib strains, and all of them belonged to a single clonal complex. A possible correlation between sequence type and ampicillin resistance was observed for Hib, while no correlations were observed for Hia. Significance and Impact of the Study: Despite H. influenzae serotype b (Hib) vaccine programs, invasive disease due to Hib still exists in Canada and is either second or third most common behind nontypeable and/or serotype a (Hia). Many previous studies on antibiotic resistance have focussed on respiratory isolates, and few have looked at resistance with regard to serotype. This study analysed antibiotic resistance in invasive Hia and Hib collected over 20 years from three provinces, and results found that significantly more Hib showed resistance compared to Hia. This provides a small snapshot of H . influenzae disease in Canada and highlights the importance to continually monitor antibiotic resistance profiles.